Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1128/mcb.9.8.3438-3446.1989
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Glucocorticoid- and Cyclic AMP-Induced Genes in T Lymphocytes

Abstract: Glucocorticoids and cyclic AMP exert dramatic effects on the proliferation and viability of murine T lymphocytes through unknown mechanisms. To identify gene products which might be involved in glucocorticoid-induced responses in lymphoid cells, we constructed a lambda cDNA library prepared from murine thymoma WEHI-7TG cells treated for 5 h with glucocorticoids and forskolin. The library was screened with a subtracted cDNA probe enriched for sequences induced by the two drugs, and cDNA clones representing 11 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…G protein-coupled receptor 83 (GPR83), first identified in murine thymoma cells as a receptor upregulated after treatment with the glucocorticoid dexamethasone (Harrigan et al, 1989;Harrigan et al, 1991;Wang et al, 2001), was later found to exhibit expression in the brain (Pesini et al, 1998;Brezillon et al, 2001). Studies reported robust GPR83 expression in regions involved in modulation of food intake (Muller et al, 2013b;Lueptow et al, 2018;Mack et al, 2019) and reward behaviors (Pesini et al, 1998;Lueptow et al, 2018;Fakira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…G protein-coupled receptor 83 (GPR83), first identified in murine thymoma cells as a receptor upregulated after treatment with the glucocorticoid dexamethasone (Harrigan et al, 1989;Harrigan et al, 1991;Wang et al, 2001), was later found to exhibit expression in the brain (Pesini et al, 1998;Brezillon et al, 2001). Studies reported robust GPR83 expression in regions involved in modulation of food intake (Muller et al, 2013b;Lueptow et al, 2018;Mack et al, 2019) and reward behaviors (Pesini et al, 1998;Lueptow et al, 2018;Fakira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%